2001
DOI: 10.1542/peds.107.4.e54
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Testing of Children for Tuberculosis: Validation of a Risk Assessment Questionnaire

Abstract: A 5-question risk assessment questionnaire completed by parents can be used to accurately identify risk factors associated with TB infection in children. In our population, some risk factors suggested by the American Academy of Pediatrics could not be validated. Parents cannot be relied on to read TST results accurately. Screening for TB can be enabled by using a standardized, validated questionnaire to identify children who should be given tuberculin skin testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 23 publications
4
54
1
1
Order By: Relevance
“…The TB risk factor questionnaire contained questions about demographics, TB exposure, work history, location of residence, and other factors shown in Table 1. This questionnaire was developed from the risk factors previously identified in the military and nonmilitary literature (20)(21)(22)(23)(24)(25), and other factors considered candidates for causal relationships with LTBI.…”
Section: Study Methodology and Proceduresmentioning
confidence: 99%
“…The TB risk factor questionnaire contained questions about demographics, TB exposure, work history, location of residence, and other factors shown in Table 1. This questionnaire was developed from the risk factors previously identified in the military and nonmilitary literature (20)(21)(22)(23)(24)(25), and other factors considered candidates for causal relationships with LTBI.…”
Section: Study Methodology and Proceduresmentioning
confidence: 99%
“…In this population, bacillus Calmette-Guérin (BCG) immunization, a TST within 12 months, and a relative with a positive TST were risk factors for a positive TST (Ն10 mm). Froehlich et al 20 performed a study to determine if a risk-assessment questionnaire could predict a positive TST in children in northern California and found that foreign birth, BCG immunization, living outside the United States, Asian or Hispanic ethnicity, or contact with a household member with TB disease or LTBI were independent predictors of LTBI.…”
Section: Screening Children and Adolescents For Risk Factors For Ltbimentioning
confidence: 99%
“…Howard and Solomon 98 demonstrated that 63% (133 of 212) of patients with positive TSTs did not report induration, although 99% (520 of 525) of those with negative TSTs correctly interpreted their skin test as negative. Froehlich et al 20 compared TST readings by parents and health care professionals. Parents failed to detect 9.9% of positive TSTs when using the 10-mm cutoff level (1% of cohort) and 5.9% of positive TSTs when using the 15-mm cutoff level (0.5% of cohort).…”
Section: Interpretation Of the Tst By Trained Health Care Workersmentioning
confidence: 99%
“…Previously, questionnaire studies have been done to assess risk factors for a positive TST in pediatric populations consisting of the middle-class insured and those of low-income, mixed ethnicity. [15][16][17][18] The main goals of our study were to (1) identify factors that are associated with a positive TST in a Mexican immigrant population; (2) evaluate Bacille Calmette-Guérin (BCG) vaccine history affect on TST results; and (3) determine whether a history of foreign visitors to the child's home, family or child travel to Mexico, and cumulative length of time of these exposures to potential active TB cases increases risks for a positive TST. …”
mentioning
confidence: 99%